1993
DOI: 10.1103/physrevb.47.9017
|View full text |Cite
|
Sign up to set email alerts
|

Persistent photoconductivity inYBa2Cu3et al.

Abstract: Persistent photoconductivity (P PC) and metastable photoinduced superconductivity, recently discovered in semiconducting YBa2Cu306+, have been investigated over the oxygen content of 0&x &1. Under exposure of semiconducting YBa,Cu306+ films (x =0.4) to visible light their resistance is found to decrease drastically. After interrupting the irradiation the resistance persists at this reduced level provided that the temperature is kept below 270 K. When the illumination dose is increased the semiconductorlike be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
140
1
1

Year Published

1997
1997
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 178 publications
(149 citation statements)
references
References 76 publications
7
140
1
1
Order By: Relevance
“…This relaxation has been observed after two kinds of activation, with light (photo-induced (super)conductivity) 12 and high pressures 13 Table I.…”
Section: Relaxation; a Simple And Direct Probe Of Classes Of Micrmentioning
confidence: 90%
“…This relaxation has been observed after two kinds of activation, with light (photo-induced (super)conductivity) 12 and high pressures 13 Table I.…”
Section: Relaxation; a Simple And Direct Probe Of Classes Of Micrmentioning
confidence: 90%
“…The photo-induced state was continuously initiated by a more than onehour illumination using the 1mW He-Ne laser with a cumulative photon dose about 10 22 photons/cm 2 , which is close to what was observed by V. I. Kudinov, etc. [5] During the illumination, the temperature of the YBCO junction was monitored by a thermocouple, and the maximum change in temperature was less than one and a half degrees (Celsius). The entire experiment was run at room temperature.…”
Section: Experimental Results and Explanationsmentioning
confidence: 99%
“…PPC and PISC of YBa 2 Cu 3 O 6+x thin films have received special attention [3][4][5][6][7][8][9], and the primary reason for this is because subsequent to visible illumination, the photo-induced state of YBa 2 Cu 3 O 6+x films has an increase in conductivity in the normal state (PPC) and an increase in the superconducting transition temperature Tc and diamagnetism in the superconducting state (PISC). It has been suggested that the PISC phenomena has several practical applications such as optically controlled superconductive switches [10].…”
Section: Introductionmentioning
confidence: 99%
“…To observe an increase in conductance, VO 2 would need to be reduced [33]. Since the beam is well localized, yet a large portion of the surface must participate to account for the photoconductance, a significant oxygen mobility would be required, which is only seen for layered or amorphous materials [34]. Therefore, if the observed PPC is associated with a structural transition, it must come in the form of a large number of narrow metallic filaments, since a single filament of the minimum required 85 nm width would still be detected.…”
Section: Discussionmentioning
confidence: 99%